First pass effect in patients with large core infarcts undergoing mechanical thrombectomy: subgroup analysis of the prospective international ASSIST registry - Hoffman, Haydn; Miralbes, Salvador; Naravetla, Bharath; Spiotta, Alejandro M.; Loehr, Christian; Martínez-Galdámez, Mario; McTaggart, Ryan A.; Defreyne, Luc; Vega, Pedro; Zaidat, Osama O.; Price, Lori Lyn; Liebeskind, David S.; et al. (Journal of neuroInterventional surgery, 2025)
Background Studies have described a first pass effect (FPE) where patients with successful recanalization after one pass experience better outcomes. Few studies have evaluated this in patients with large core infarctions. - Objective To determine whether patients with large core infarcts undergoing mechanical thrombectomy in which first pass reperfusion is achieved experience improved outcomes compared with those who undergo more than one pass. - Methods The ASSIST Registry, a prospective, global, multicenter registry of patients with anterior circulation large vessel occlusion (LVO) undergoing mechanical thrombectomy was used. Adults with internal carotid artery/M1/M2 occlusions and preprocedural Alberta Stroke Program Early CT Score (ASPECTS) <6 were included. The variable of interest was number of thrombectomy passes (dichotomized to 1 or >1) performed for the target occlusion. The primary outcome was 90-day good functional outcome defined as modified Rankin Scale (mRS) score 0-3. - Results 150 patients with a mean age of 66 years were included. Most patients had ASPECTS of 4 (33%) or 5 (59%). 77 patients (51%) underwent one pass. Compared with patients with one pass, those with more than one pass had significantly lower odds of good functional outcome (OR=0.44, 95% CI 0.21 to 0.93; P=0.03). More than one pass was not significantly associated with 90-day mRS score 0-2 (OR=0.46, 95% CI 0.15 to 1.43; P=0.17) or mortality (OR=2.03, 95% CI 0.81 to 5.08; P=0.13). FPE (one pass eTICI≥2c) and modified FPE (one pass extended thrombolysis in cerebral infarction ≥2b50) were not significantly associated with 90-day mRS 0-3, mortality, or symptomatic intracranial hemorrhage. - Conclusion This analysis suggests that use of multiple passes is associated with worse outcomes in patients with large core infarcts.
Gesehen am 25.07.2025